2021
DOI: 10.1111/ane.13417
|View full text |Cite
|
Sign up to set email alerts
|

The potential neurological effect of the COVID‐19 vaccines: A review

Abstract: The coronavirus disease 2019 caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a pandemic with people infected in almost all countries. The most efficient solution to end this pandemic is a safe and efficient vaccine. Classic platforms are used to develop vaccines including live-attenuated vaccine, inactivated vaccine, protein subunit vaccine, and viral vector. Nucleic acid vaccine uses next-generation platforms for their development. Vaccines are now rushing to the market. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 51 publications
1
92
1
1
Order By: Relevance
“…COVID -19 is a systemic disease condition that can lead to various systemic complications affecting almost any system in the body. Recently, different types of COVID-19 vaccines have been distributed worldwide; however, despite the updated studies on these vaccines and their safety, there are several registered complications that can be related to the vaccine [ 1 ]. Neurological complications, such as autoimmune encephalitis, demyelination diseases, Guillain‐Barré syndrome (GBS), seizures, and acute encephalopathy, have been reported in patients who received the COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…COVID -19 is a systemic disease condition that can lead to various systemic complications affecting almost any system in the body. Recently, different types of COVID-19 vaccines have been distributed worldwide; however, despite the updated studies on these vaccines and their safety, there are several registered complications that can be related to the vaccine [ 1 ]. Neurological complications, such as autoimmune encephalitis, demyelination diseases, Guillain‐Barré syndrome (GBS), seizures, and acute encephalopathy, have been reported in patients who received the COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The only speculated mechanism underlying the development of seizures after vaccinations in the literature was a vaccination-induced fever that acts as a seizure trigger. ( Lu et al, 2021 ) However, our patient was a healthy non-epileptic nurse who developed NORSE as a first presentation only ten days following the first vaccine dose. This makes the fever theory less likely and prompts the search for more integral mechanisms related to the role of pro-inflammatory cytokines in the pathogenesis of post-vaccination epilepsy.…”
Section: Discussionmentioning
confidence: 81%
“…11 While associations have been made about vaccinations and autoimmunity, the mechanisms behind these are yet to be clearly understood. 12 A recent review 13 of potential neurological effects of SARS-CoV-2 vaccinations summarised the current reported neurological adverse events in patients who have received the different types of vaccination and found that only one case of transverse myelitis was deemed to have been associated with SARS-CoV-2 vaccination. In that particular case, the patient was injected with a non-replicating viral vector-based vaccine (ADZ1222).…”
Section: Discussionmentioning
confidence: 99%